Rapid amplification of cDNA ends and cDNA screening of alcohol dehyrdrogenase genes from metroxylon sagu - Norzainizul, Julai @Julaihi (Universiti Malaysia Sarawak, UNIMAS, 2008)
Metroxylon sagu is one of the most important crops that found abundantly in Sarawak especially in freshwater swamp area where it facing environmental stress such as flooding that causing metabolisms changing in the cell. One of the important gene encodes during this stress period is alcohol dehydrogenase (Adh) gene which involve in fermentation metabolism in attempt to produce energy without presence of oxygen. The objective of this study was to isolated full length of Adh gene through RACE. RNA from waterlogged roots and leaves of M. sagu was extracted and first strand cDNA was develop form it and then undergo PCR process with using specific primer in attempt to extract Adh gene. Combination of ADH primer 1 and 3’ inner primer produced reliable PCR product which undergo gel extraction to obtain pure product which subsequently sent for DNA sequencing purpose. The result was not the desired Adh gene due to BLAST search and several other attempt was done in screening for Adh gene using other primers. Only screening done by using combination of primer PMB Adh1-f/r gives PCR product gave result at 250 bp at range 40-50oC.